Meso-Analysis of Recycled Coarse Aggregate Self-Compacting Concrete on the Basis of Random Aggregate Model - Songpu Gao; Qing Liu; Fengxia Han; Zhongyan Guo; Jianping Yang; Jianwei Ren (Advances in Materials Science and Engineering)
The purpose of this paper is to explore the numerical simulation of damage process and results of a new environmentally friendly material, recycled coarse aggregate self-compacting concrete (RCASCC). Random aggregate model of mesoscopic viewpoint was used for the experimental simulation of RCASCC. Results show that the specimens with 50% substitution rate exhibited the best performance among the specimens (i.e., with rates of 25%, 50%, 75%, and 100%). The stress-strain curves after dimensionless treatment were fitted using the uniaxial compressive principal equation of concrete with control parameters a = 0.9 and b = 11, and the fitting degree of the curve was relatively good. Meanwhile, the change process of internal cracking was shown intuitively. The crack expansion process became more obvious in the specimens and beams with a high substitution rate of RCA. The simulation results of the bending process of RCASCC beams analyzed by the concrete damaged plasticity (CDP) model and extended finite element (XFEM) were compared with the test results. Both simulation results validated the applicability of the CDP model and XFEM in the mechanical tests of RCASCC and can provide valuable reference for future research on the mechanical properties of recycled aggregate self-compacting concrete.